Androgen metabolism and inhibition of interleukin-1 synthesis in primary cultured human synovial macrophages - M. Cutolo; S. Accardo; B. Villaggio; A. Barone; A. Sulli; E. Balleari; C. Bason; L. Felli; O. M. Granata; R. Amodio; L. Castagnetta (Hindawi Limited, 1995)
The presence of androgen receptors on synovial macrophages in human normal and rheumatoid synovial tissues has been described previously. It is now reported that primary cultured human macrophages obtained from normal and rheumatoid synovia express functional androgen receptors. We have investigated the capacity of cultured macrophages to metabolize androgens and have found that these cells were capable of metabolizing testosterone to the bioactive metabolite dihydrotestosterone. Therefore, macrophages contain the key enzymes of steroidogenesis, in particular the 5α-treductase. Furthermore, interleukin-1β production by primary cultured rheumatoid macrophages was analysed, following exposure to physiological concentrations of testosterone (10−8 M). A significant decrease of IL-1β levels in conditioned media after 24 h (p < 0.05) was observed. It is concluded that androgens may act directly on human macrophages and may interfere with some of their functions via receptor-dependent mechanisms.